A new species and species richness distribution of the gypsophyte butterworts (Pinguicula, Lentibulariaceae) in Mexico - Jorge David López-Pérez; Sergio Zamudio; Aarón Rodríguez; Guadalupe Munguía-Lino (Botan‪ical Sciences, 2025)
Background: Mexico harbours the highest species richness of Pinguicula, with 54 species. Plants collected on gypsum soils in Oaxaca do not coincide with any known species.